2004
DOI: 10.1149/1.1644609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Slurry Ionic Salts at Dielectric Silica CMP

Abstract: The effects of alkaline ionic salts on silica chemical mechanical polishing ͑CMP͒ have been studied. Particle size, zeta potential, and stability via turbidity tests have been characterized. Particle size and size distributions have been found to increase with ionic strength for three types of alkaline ionic salts due to the decrease in the magnitude of the zeta potential of silica slurry due to the addition of alkaline ionic salts. Slurry stability measured by turbidity tests showed two regimes of slurry stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 22 publications
6
48
0
Order By: Relevance
“…Adding 0.25 wt% K 2 SO 4 , the oxide RRs increased throughout the pH range, presumably due to the increase in ionic strength. Several studies [19][20][21][22][23] have already shown that increasing the ionic strength increases oxide RRs due to the reduction in the electrostatic repulsion, an argument also supported by the potential data for the silica dispersions (later shown in Fig. 4).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Adding 0.25 wt% K 2 SO 4 , the oxide RRs increased throughout the pH range, presumably due to the increase in ionic strength. Several studies [19][20][21][22][23] have already shown that increasing the ionic strength increases oxide RRs due to the reduction in the electrostatic repulsion, an argument also supported by the potential data for the silica dispersions (later shown in Fig. 4).…”
Section: Resultssupporting
confidence: 60%
“…In the case of K 2 SO 4 , however, the counter ions, K + , interact with silica surfaces, as suggested by the potential data. The adsorbed cations, as suggested by Choi et al [22], enable more abrasive particles to come into contact with the wafer surface leading to an increase in the oxide RRs. Also, the adsorbed cations interact with the negatively charged Si O − on the surface and weaken the underlying Si O Si bonds as suggested by Kawano et al [42][43][44].…”
Section: Effect Of the Additive Adsorption On Oxide And Nitride Rrsmentioning
confidence: 94%
“…Ramarajan et al demonstrated CMP with high ionic strength slurries at high pH due to the reduction of electrostatic repulsion force [23]. The effects of alkaline ionic salts (KCl, LiCl and NaCl) on SiO 2 CMP using 500 nm diameter abrasive silica particles are reported by Choi et al [24]. Adsorption of surfactants at the solidliquid interface has been studied for many years, but application of surfactants in the field of microelectronics device fabrication has been restricted primarily to the stabilization of particulate dispersions in CMP slurries and wet cleaning.…”
Section: Introductionmentioning
confidence: 96%
“…30,34,35,37 In addition to the effect on the wafer hardness, slurry chemicals have also been shown to influence the zeta potential of abrasive particles and the wafer, 27,29,35,[39][40][41][42] where the slurry pH was the primary factor affecting the zeta potentials. 43 The slurry pH and zeta potentials of particles and wafer surface could significantly affect the polishing performance.…”
mentioning
confidence: 99%